Evaluation on Sale Banana (Musa paradisiaca L.) Drying on Hybrid (Solar-Electricity) Tray Dryer - Arief Fazlul Rahman; - Sukmawaty; Rahmat Sabani (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2017)
Hybrid (solar-electricity) dryer use additional heat from heater, therefore its efficiency is higher than the solar one. This research aimed to evaluate energy requirement during the drying process and to study efficiency of drying chamber of hybrid (solar-electricity) tray type dryer to drying Sale Banana. Method used was experimental. Material used was banana sliced 0.8 cm and 0.4 cm thickness. Research parameters consist of temperature, moisture content, drying time, drying energy, air flow velocity, and solar intensity. Analyzed data were drying energy produced by the collector, energy to evaporate water in the material, efficiency of drying chamber, and energy to increase material’s temperature. Data analysis conducted using Microsoft excel. This hybrid dryer is suitable for Sale Banana drying with drying chamber’s optimum temperature of 55°C. The result showed that the best drying process using hybrid dryer obtained with material thickness of 0.4 cm, whereas maximum efficiency of solar dryer was 42.21%. Keywords: heater, collector, drying, banana ABSTRAK Pada alat pengering hybrid (surya-listrik) digunakan panas tambahan dari heater, sehingga efisiensi hybrid lebih tinggi dari full surya. Penelitian ini bertujuan untuk mengevaluasi kebutuhan energi selama pengeringan serta mempelajari efisiensi ruang pengering alat pengering hybrid (surya-listrik) tipe rak untuk pengeringan pisang sale. Metode yang digunakan adalah eksperimental. Bahan yang digunakan dalam penelitian ini adalah pisang hijau yang diiris tipis 0,8 cm dan 0,4 cm. Parameter penelitian terdiri dari suhu, kadar air, lama pengeringan, energi pengeringan, kecepatan aliran udara dan intensitas cahaya matahari. Data yang dianalisa pada penelitian ini adalah energi pengeringan yang dihasilkan oleh kolektor, energi untuk menguapkan air bahan, efisiensi ruang pengering, dan energi untuk menaikan suhu bahan. Analisis data dilakukan menggunakan microsoft excel. Alat pengering hybrid (surya-listrik) tipe rak ini cocok untuk pengeringan pisang sale dengan suhu optimal pada ruang pengering adalah 55oC pada pengeringan hybrid. Hasil penelitian menunjukan proses pengeringan pisang sale terbaik adalah dengan ketebalan bahan 0,4 cm menggunakan hybrid dengan efisiensi ruang pengering maksimal 55,20% dengan kadar air 35,5% sementara efisiensi maksimal pengeringan surya sebesar 42,21%. Kata kunci: heater, kolektor, pengeringan, pisang